2015
DOI: 10.5653/cerm.2015.42.3.111
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of granulosa cells in the maturation rate of immature human oocytes and embryo development: A co-culture study

Abstract: ObjectiveIn order to increase the number of mature oocytes usable for intracytoplasmic sperm injection (ICSI), we aimed to investigate the effect of co-culturing granulosa cells (GCs) on human oocyte maturation in vitro, the fertilization rate, and embryo development.MethodsA total of 133 immature oocytes were retrieved and were randomly divided into two groups; oocytes that were cultured with GCs (group A) and oocytes that were cultured without GCs (group B). After in vitro maturation, only oocytes that displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
(51 reference statements)
1
27
1
1
Order By: Relevance
“…Culture of COCs in medium containing granulosa secreted factors has been suggested to increase the proximity of in vitro culture to in vivo condition and improve the efficiency of in vitro oocyte maturation, especially in COCs derived from small follicles (2 to � 4mm) with lower developmental competence compared to follicles of � 4 to 6mm or of greater size [29,30]. Our goal is to select ovine as a model for human IVM in future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Culture of COCs in medium containing granulosa secreted factors has been suggested to increase the proximity of in vitro culture to in vivo condition and improve the efficiency of in vitro oocyte maturation, especially in COCs derived from small follicles (2 to � 4mm) with lower developmental competence compared to follicles of � 4 to 6mm or of greater size [29,30]. Our goal is to select ovine as a model for human IVM in future studies.…”
Section: Introductionmentioning
confidence: 99%
“…In various animal models, the coculture with somatic cells (granulosa, oviductal or embryonic fibroblasts) as companion cells or monolayer, or the culture in isolated oviducts, gave promising results in terms of nuclear and cytoplasmic oocyte maturation (Chigioni, Perego, & Luvoni, ; Lee, Quaas, Wright, Toth, & Teixeira, ; Luvoni, Chigioni, Allievi, & Macis, ). The cleavage, as well as the advanced embryo development, were also enhanced when COCs were matured with companion cells, rather than alone (Hatoya et al., ; Jahromi, Mosallanezhad, Matloob, Davari, & Ghobadifar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory molecules, glucose metabolites, nucleotides, and amino acids are known to be transferred through the oocyte-GC gap junctions of growing oocytes [31]. GCs were demonstrated to have a considerable improvement in the maturation rate and the likelihood of embryo development [21]. Our data performed the potential mechanism in GCs to provide some evidences linking obesity to poor reproductive outcomes pregnancy outcome.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, it is known that GCs can protect the oocyte against oxidative stress [20]. In vitro study demonstrated that culturing immature human oocytes with GCs improves the maturation rate and the likelihood of embryo development [21].…”
Section: Introductionmentioning
confidence: 99%